Rhapsodic Objects Art, Agency, and Materiality (1700-2000) - Etienne, Noemie; Biro, Yaelle (Contact Zones, 2021)
Circulation and imitation of cultural products are key factors in shaping the material world.The contributions explore how technical knowledge, immaterial desires, and political agendas impacted the production and consumption of visual and material culture in different times and places. They map a new a multidirectional market for cultural goods in which the source countries can be positioned at the center.